Boko Haram Insurgency, Youth Mobility and Better Life in the Far North Region of Cameroon - Afu,Isaiah Kunock (2019)
This article portrays youth mobility in Cameroon as a means to escape poverty and to achieve a better life. Youth mobility though not new is, however, taking a new dimension as a result of Boko Harams violent conflict. To explore how this violence has affected mobility, this study analyses narration of youngsters escape experiences from Boko Haram and their ideas of how to achieve a better life, drawing on interviews in Cameroons Far North Region. The study begins with the origin and regionalisation of Boko Haram, followed by the concept of youth, the evolution of mobility trends and better life. It then proceeds to narrations of escape experiences, places of destination and sheds light on mobility pathways and integration dynamics.